(untitled) (Artology: Studies in the Arts, 2025)
This essay explores how the concept of infinity is made visible and tangible in art, taking as its point of departure Infinite Cube by Antony Gormley—a work inspired by the designs and vision of Gabriel Mitchell. Through this collaborative and commemorative object, the essay reflects on how the infinite appears within the finite, drawing connections between artistic form, embodied perception, and mathematical abstraction. It weaves together historical and contemporary examples—from Renaissance perspective and Blake’s “infinite particular” to Yayoi Kusama’s immersive environments and speculative geometry—to argue that art offers a privileged site for encountering infinity not as abstraction, but as sensuous and relational experience. Combining personal narrative, critical theory, and visual analysis, the essay foregrounds the role of art in mediating between the cosmic and the intimate, the conceptual and the concrete.